Guillem Colom-Montero, «Monzó and Contemporary Catalan Culture 1975-2018 Cultural Normalization, Postmodernism and National Politics», Cambridge, Legenda, 2021, 226 p. - Ojeda Caba, Júlia (Caplletra. Revista Internacional de Filologia, 2022)
Ressenya sobre el llibre de Guillem Colom-Montero, Quim Monzó and Contemporary Catalan Culture 1975-2018 Cultural Normalization, Postmodernism and National Politics, Cambridge, Legenda (Studies in Hispanic and Lusophone Cultures 45 / Modern Humanities Research Association), 2021, 226 p., ISBN: 978-1-78188-392-1.